Differences in mushroom bodies morphogenesis in workers, queens and drones of Apis mellifera: Neuroblasts proliferation and death - Roat, Thaisa Cristina [UNESP]; Landim, Carminda da Cruz [UNESP] (Pergamon-Elsevier B.V. Ltd, 2010)
Apis mellifera is an interesting model to neurobiological studies. It has a relatively small brain that commands the complex learning and memory tasks demanded by the social organization. An A. mellifera colony is made up of a queen, thousands of workers and a varying number of drones. The latter are males, whereas the former are the two female castes. These three phenotypes differ in morphology, physiology and behavior, correlated with their respective functions in the society. Such differences include the morphology and architecture of their brains. To understand the processes generating such polymorphic brains we characterized the cell division and cell death dynamics which underlie the morphogenesis of the mushroom bodies, through several methods suitable for evidence the time and place of occurrence. Cell death was detected in mushroom bodies of last larval instar and mainly in black-eyed pupae. Cell division was observed in mushroom bodies, primarily at the start of metamorphosis, exhibiting temporal differences among workers, queens and males. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Nervous system; Bee; Apoptosis; Mitosis; Brain